Design of LNA at 5.8GHz with Cascode and Cascaded Techniques Using T-Matching Network for WiMAX Applications - Ibrahim, A.B; Othman , A.R; Hussain , M.N; Johal , M.S (UTEM, 2011)
This project presents a 5.8 GHz Low Noise Amplifier (LNA) design with cascode and cascaded techniques using T-matching network applicable for IEEE 802.16 standard.The amplifier uses the FHX76LP Low Noise SuperHEMT FET. The design simulation process is done by using the Advance Design System (ADS) software. The cascode and cascaded low noise amplifier (LNA) produces a gain of 53.4dB and noise figure (NF) of 1.2dB. The input reflection (S11) and output return loss (S22) are -24.3dB and -23.9dB respectively. The input sensitivity is complying with the IEEE 802.16 standards.